Sistem Pakar Diagnosa Penyakit Infeksi Saluran Pernapasan Akut (ISPA) Menggunakan Metode Forward Chaining Berbasis Website - Sholahuddin; Shelvi Eka Tassia (shofanah Media Berkah, 2026)
Acute Respiratory Tract Infection (ARI) is a common health problem that requires prompt and appropriate treatment. Diagnosis is often challenging, especially for laypeople without medical knowledge. This study aims to develop a website-based expert system for diagnosing ARI using the Forward Chaining method. This system works by matching symptoms inputted by the user with rules contained in a knowledge base to generate a relevant diagnosis. This system is implemented as a web application, making it easily accessible through any internet-connected device without the need to download additional applications. System evaluation was conducted through black-box testing to ensure its functionality meets user needs. Based on a literature review, this system is expected to help users obtain initial information about ARI.